Growth and Survival Rate of Siamese Catfish (Pangasius hypopthalmus) in Recirculation Systems with Different Water Discharge - Afrinaldi '; Mulyadi '; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The aims of the research was to know the growth performance and survival rate of Catfish (Pangasius hypopthalmus) in recirculation system with different water discharge. The method used was the experimental method with 5 treatments and 3 replications. The treatments were P0 = control (without water discharge), P1 = 0,22 litres/second, P2 = 0,33 litres/ second, P3 = 0,36 litres/ second, P4 = 0,50 litres / second. The particular size of the Siamese Catfish were used around 5-6 cm were reared for 45 days in the tarpaulin cube tank (50 x 50 x 50) cm³ with 30 fishes/tank of fish stocking density. The fish were fed by adsatiation three times a day. The result shows that the best treatment is in the P4 which water discharge 0,50 liter/second which contributed to the 3,81% of specific growth rate; 4,5 gram of absolute weight growth; 3,29 cm of absolute length growth and 90,54 of food efficiency. Meanwhile, the highest survival rate was given by the treatments in P0 and P1 which was 100%. The best water quality parameter was shown in P4 (water discharge 0,50 liter/second) where ammonia (NH3) was 0,015-0,059 mg/l, temperature was 27,2-28,9º C, pH was 6,1-6,4, dissolved oxygen (DO) was 5,68-6,13 mg/l, nitrit was 0,06-0,23 mg/l, and nitrat was 0,86-093mg/l.Keyword: Pangasius hypopthalmus, Water discharge, Growth Performance, Survival Rate